2016
DOI: 10.1109/jstars.2016.2570424
|View full text |Cite
|
Sign up to set email alerts
|

L-Band Passive and Active Signatures of Vegetated Soil: Simulations With a Unified Model

Abstract: The synergistic exploitation of L-band active and passive measurements has received increasing interest. In this paper, both theoretical simulations and experimental data are employed to get a deeper insight into the relations between the backscattering coefficient and the emissivity. An active/passive discrete model is used to simulate the backscattering coefficient and the emissivity of bare soil, maize crop of various heights, and deciduous forests of various biomass values. Volumetric soil moisture is vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…An inverse relationship was found between CyGNSS and SMAP passive observations with SMC, which in turns reflects the expected sensitivity to changes in the dielectric constant of the soil [67]. This functional relationship between both types of sensors is different from that associated with previous SAR-based studies [61], [68]. The tau-omega model (14) under the assumption T S ≈ T v ≈ α, where α is the coefficient of regression, was used to fit the scatter plots of Γ rl versus T I /2 (see Figs.…”
Section: Table II Latitude and Longitude Of The Selected Target Areasmentioning
confidence: 71%
“…An inverse relationship was found between CyGNSS and SMAP passive observations with SMC, which in turns reflects the expected sensitivity to changes in the dielectric constant of the soil [67]. This functional relationship between both types of sensors is different from that associated with previous SAR-based studies [61], [68]. The tau-omega model (14) under the assumption T S ≈ T v ≈ α, where α is the coefficient of regression, was used to fit the scatter plots of Γ rl versus T I /2 (see Figs.…”
Section: Table II Latitude and Longitude Of The Selected Target Areasmentioning
confidence: 71%
“…In some cases this leads to the inclusion of some observations in multiple grid cells (this accounts for less than 1% of the observations), while observations that are not within this distance to a grid point are excluded from the study. More detailed information on the gridding scheme can be found in Konings et al [25], McColl et al [35], and Piles et al [34].…”
Section: A Aquarius/sac-dmentioning
confidence: 99%
“…However, although multisensor techniques gain more and more importance, few studies have compared active and passive microwave vegetation parameters at the global scale using space-borne data. Guerriero et al [35] compared L-band backscattering coefficients and emissivity from theoretical simulations and airborne and space-borne experiments in the presence of different vegetation covers. Konings et al [25] compared VOD to HV-backscattering and to the radar vegetation index (RVI) using three years of global Aquarius observations and found more scatter in the relationship between VOD and RVI than between VOD and the HV backscattering coefficient.…”
mentioning
confidence: 99%
“…Physical interpretation of simultaneous active and passive microwave signals has been pursued by investigators (e.g. Chauhan et al, 1994;Ferrazzoli et al, 1989;Guerriero et al, 2016;Dente et al, 2014;Wang et al, 2018]) as well. Chauhan et al (1994) demonstrated that a discrete scatter approach can be used to predict both L-band radar and radiometer observations.…”
mentioning
confidence: 99%
“…Dente et al (2014) investigated a discrete electromagnetic model for simulating C-band Advanced Microwave Scanning Radiometer for EOS (AMSR-E) brightness temperature (T b ) and ASCAT backscattering coefficient ( ) in the Maqu area and proved its applicability to satellite observations. Guerriero et al (2016) applied a discrete electromagnetic model to reproduce the active and passive observations simultaneously collected in airborne field campaigns at L band.…”
mentioning
confidence: 99%